Future directions for therapeutic strategies in post-ischaemic vascularization: a position paper from European Society of Cardiology Working Group on Atherosclerosis and Vascular Biology. Issue 11 (17th July 2018) - Caporali, Andrea; Bäck, Magnus; Daemen, Mat J; Hoefer, Imo E; Jones, Elizabeth A; Lutgens, Esther; Matter, Christian M; Bochaton-Piallat, Marie-Luce; Siekmann, Arndt F; Sluimer, Judith C; Steffens, Sabine; Tuñón, José; et al.
Abstract: Modulation of vessel growth holds great promise for treatment of cardiovascular disease. Strategies to promote vascularization can potentially restore function in ischaemic tissues. On the other hand, plaque neovascularization has been shown to associate with vulnerable plaque phenotypes and adverse events. The current lack of clinical success in regulating vascularization illustrates the complexity of the vascularization process, which involves a delicate balance between pro- and anti-angiogenic regulators and effectors. This is compounded by limitations in the models used to study vascularization that do not reflect the eventual clinical target population. Nevertheless, there is a large body of evidence that validate the importance of angiogenesis as a therapeutic concept. The overall aim of this Position Paper of the ESC Working Group of Atherosclerosis and Vascular biology is to provide guidance for the next steps to be taken from pre-clinical studies on vascularization towards clinical application. To this end, the current state of knowledge in terms of therapeutic strategies for targeting vascularization in post-ischaemic disease is reviewed and discussed. A consensus statement is provided on how to optimize vascularization studies for the identification of suitable targets, the use of animal models of disease, and the analysis of novel delivery methods.